Clinical and Immunological Characteristics of Human Infections With H5N6 Avian Influenza Virus. (16th August 2018) - Bi, Yuhai; Tan, Shuguang; Yang, Yang; Wong, Gary; Zhao, Min; Zhang, Qingchao; Wang, Qiang; Zhao, Xiaonan; Li, Liqiang; Yuan, Jing; Li, Hao; Li, Hong; et al.
Abstract: Background: H5N6 avian influenza virus (AIV) has caused sporadic, recurring outbreaks in China and Southeast Asia since 2013, with 19 human infections and 13 deaths. Seventeen of these infections occurred since December 2015, indicating a recent rise in the frequency of H5N6 cases. Methods: To assess the relative threat of H5N6 virus to humans, we summarized and compared clinical data from patients infected with H5N6 (n = 19) against data from 2 subtypes of major public health concern, H5N1 (n = 53) and H7N9 (n = 160). To assess immune responses indicative of prognosis, we compared concentrations of serum cytokines/chemokines in patients infected with H5N6, H5N1, H7N9, and 2009 pandemic H1N1 and characterized specific immune responses from 1 surviving and 2 nonsurviving H5N6 patients. Results: H5N6 patients were found to have higher incidences of lymphopenia and elevated alanine aminotransferase and lactate dehydrogenase levels compared with H5N1 and H7N9 patients. Hypercytokinemia was detected at substantially higher frequencies from H5N6 patients compared to those infected with other AIV subtypes. Evaluation of adaptive immunity showed that both humoral and cellular responses could be detected in the H5N6-infected survivor, but cellular responses were absent in the nonsurvivors. In addition, the surviving patient had lower concentrations of both pro- and anti-inflammatory cytokines/chemokines compared to the nonsurvivors. Conclusions: Our results support that H5N6 virus could potentially be a major public health threat, and suggest it is possible that the earlier acquisition of cellular immunity and lower concentrations of cytokines/chemokines contributed to survival in our patient. Analysis of more patient samples will be needed to draw concrete conclusions. Abstract : Analysis of the clinical data from patients shows that H5N6 virus is a potential public health threat. Analysis of samples from 1 human survivor vs 2 nonsurvivors shows that an earlier acquisition of cell-mediated response and lower concentrations of cytokines/chemokines may have contributed to survival.